2016
DOI: 10.1128/jvi.01399-16
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinvasion of α-Synuclein Prionoids after Intraperitoneal and Intraglossal Inoculation

Abstract: ABSTRACTα-Synuclein is a soluble, cellular protein that in a number of neurodegenerative diseases, including Parkinson's disease and multiple system atrophy, forms pathological deposits of protein aggregates. Because misfolded α-synuclein has some characteristics that resemble those of prions, we investigated its potential to induce disease after intraperitoneal or intraglossal challenge injection into bigenic Tg(M83+/−:Gfap-luc+/−) mice, which express the A53T mutant of human α-synuclein and firefly luciferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 54 publications
(58 reference statements)
7
75
1
1
Order By: Relevance
“…; Breid et al . ). The hypothesis of the present study is that M83 disease can be accelerated by the intraperitoneal inoculation of sick M83 brain homogenates and that the accumulation of α‐syn P in the central nervous system may depend on the initial level of expression of the normal α‐syn protein in the mouse brain.…”
mentioning
confidence: 97%
“…; Breid et al . ). The hypothesis of the present study is that M83 disease can be accelerated by the intraperitoneal inoculation of sick M83 brain homogenates and that the accumulation of α‐syn P in the central nervous system may depend on the initial level of expression of the normal α‐syn protein in the mouse brain.…”
mentioning
confidence: 97%
“…Our findings support a recent study which also demonstrated the ability for ␣S fibrils, i.p. injected in transgenic mice expressing the A53T ␣S protein, to induce ␣S pathology and paralysis (50). Although the latter study provides insight into the potential efficiency of this peripheral route, we provide a higher powered study and include a number of control proteins which aim to better understand the component responsible for ␣S pathology and disease induction.…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains to be supported, a role for microglia and other immune cells in such periphery-to-CNS propagation of aggregated α-syn cannot be discounted. Indeed, the transmission of α-syn from the periphery into the brain is often accompanied by increased microglial activity and neuroinflammation (Breid et al 2016). To sum up, circulating glial cells may play various roles in the spread of excess aggregated α-syn, either over short or long distances.…”
Section: Do Non-neuronal Cells Play a Role In Neuron To Neuron Transmmentioning
confidence: 99%